Efektivitas Pemberian Pupuk Organik Cair Dari Limbah Kulit Pisang Kepok (Musa Parasidiaca) Terhadap Pertumbuhan Tanaman Sawi Hijau - Hadi Jaya Putra, Sukarman; Marselinus Sole Tereng, Pankrasius; Gratia Aprilia, Maria; Trasia Sona, Anne; Dua Lina, Olivia; Novianti, Kristina; Hingi Koten, Patrisia; Dua Rina, Veronika; Agnes Yunita, Yuliana; Anjelina Enggona, Maria; Indra, Yosef; Nika, Kristina; Yanseli, Martha (Jurnal Biogenerasi, 2024)
The aim of this research is to determine the effect of using organic fertilizer from kepok banana peel waste (Musa parasidiaca) as liquid organic fertilizer on the growth of mustard greens (Brassica juncea L). This research used a Completely Randomized Design (RAL) with 3 treatments and 1 treatment. without fertilizer and 1 treatment using liquid organic fertilizer from kepok banana peel with a volume of 240 mL, and 1 treatment with a mixture of 120 mL of fertilizer and 120 mL of water, then repeated 5 times for a total of 15 experimental units with the parameters measured being plant height, number of leaves, leaf length, and leaf width. The results of the study showed that the use of banana peel liquid organic fertilizer doses at a dose of 240 mL of liquid fertilizer, 240 mL of a mixture of liquid fertilizer and water, and 240 mL of water without a mixture of liquid fertilizer were significantly different between the first measurement after 12 HST with the second measurement 19 HST.